2008
DOI: 10.1158/1078-0432.ccr-07-1216
|View full text |Cite
|
Sign up to set email alerts
|

TACE/ADAM-17: A Component of the Epidermal Growth Factor Receptor Axis and a Promising Therapeutic Target in Colorectal Cancer

Abstract: Purpose: Activation of the epidermal growth factor receptor (EGFR) requires cell surface cleavage of EGFR ligands, uptake of soluble ligand by the receptor, and initiation of EGFR tyrosine kinase activity. We define these collective events as the EGFR axis. Transforming growth factor-a (TGF-a) and amphiregulin are two EGFR ligands that are delivered preferentially to the basolateral surface of polarized epithelial cells where the EGFR resides. TACE/ADAM-17 (tumor necrosis factor-a converting enzyme/a disintegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 32 publications
(29 reference statements)
3
84
0
Order By: Relevance
“…57). WAY-022, which is a selective inhibitor of ADAM-17, was found to decrease DNA replication and cell growth in colorectal cancer cells (57). Furthermore, the combination of suboptimal concentrations of WAY-022 with an EGFR monoclonal antibody or a selective EGFR kinase inhibitor resulted in cooperative growth inhibition (57).…”
Section: Adams As Targets For Anticancer Therapiesmentioning
confidence: 99%
“…57). WAY-022, which is a selective inhibitor of ADAM-17, was found to decrease DNA replication and cell growth in colorectal cancer cells (57). Furthermore, the combination of suboptimal concentrations of WAY-022 with an EGFR monoclonal antibody or a selective EGFR kinase inhibitor resulted in cooperative growth inhibition (57).…”
Section: Adams As Targets For Anticancer Therapiesmentioning
confidence: 99%
“…Tanaka et al (2005) found that ADAMl7 can mediate the release of specific EGFR ligands, which can bind to epidermal growth factor and activate the EGFR to cause epithelial hyperplasia disorder and then develop into cancer. A previous study found that ADAMselective protease inhibitors could block the EGFR pathway in tumor cells (Merchant et al, 2008). Currently, the EGFR signaling pathway is a known target of anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is a key transmembrane glycoprotein triggering a network of downstream signaling pathways, including not only cell proliferation, cell-cell adhesion and migration, but also the invasion of the tumor front, apoptosis and DNAdamage repair in neoplasm cells (8)(9)(10). Over-expression of EGFR and its ligands, such as EGF, TGF·, amphiregulin and the presence of tyrosine kinase domain mutations have been noted in many human cancer types, such as HNSCC (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of malignancies of epithelial origin have been characterized by the overexpression of EGFR and/or its ligands, such as epidermal growth factor (EGF), transforming growth factor-· (TGF·) and amphiregulin (11,12). The amplification of genes encoding EGFR has also been noted in previous studies (13)(14)(15).…”
Section: Introductionmentioning
confidence: 94%